Neuromodulação e traumatismo cranioencefálico: quais as barreiras? Neuromodulation and traumatic brain injury: what the barriers? (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2023)
Editorial
Keywords: Neuromodulação; traumatismo cranioencefálico